Preliminary studies on the antimicrobial properties of buchholzia coriacea (wonderful kola) (2009)
"In this work, the antimicrobial properties of fresh Buchholzia Coriacea (wonderful kola) and its extracts was investigated. The proximate composition of the fresh kola was also determined. B. coriacea was dried, milled and extracted using two different solvents of varying polarity: hexane and methanol. The effect of the fresh kola, hexane and methanol extracts was tested on some food borne pathogens. This was evaluated by measuring the zone of inhibition on nutrient agar for bacteria and malt extract agar for fungi. The food borne pathogens used in this study are Esherichia coli, Enterococcus faecalis, Staphylococcus aureus, Trichoderma viride and Aspergillus niger. The proximate composition showed that the fresh kola consists of 53.13% moisture, 9.8% ash, 3.46% crude fibre, 2.20% fat, 13.22% crude protein and 28.19% carbohydrate. The fresh kola showed inhibitory zones with the test bacteria: E. coli (62 mm), E. faecalis (40 mm) and S. aureus (50 mm). The growth of the two test fungi T. viride and A. niger was completely inhibited. The hexane extract showed inhibitory zones ranging from 20 to 40 mm with the test bacteria: E.coli (21 mm), E. faecalis (20 mm) and S. aureus (40 mm). It however showed no inhibitory effect on T. viride and A. niger. The methanolic extract of B. coricea also showed inhibitory zones ranging from 20 to 30 mm with some of the test pathogens: E.coli (30 mm), E. faecalis (25 mm) and S. aureus (20 mm), T. viride (15 mm). It however showed no inhibitory effect on A. niger. "